ANALISIS WACANA ARTIKEL PADA MAJALAH BERBAHASA JEPANG BERDASARKAN ASPEK KOHESI - Adek Warnengsih; Sri Wahyu Widiati; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to determine aspects of discourse cohesion aspect Japanese language magazine articles in both grammatical cohesion and cohesion lexical. This research used qualitative approach and analyzed by Halliday & Hasan theory and Kridalaksana theory. Research object were taken from the Japanese language magazine which is two articles written by readers of the magazine Tanoyaku April 2016 edition of volume 144. Data collection’s method was “simak” method and used “simak bebas libat cakap” technic and taking note technic. The method is not only noted the use of verbal language but also the use of language of writing. The result shows that the data on the grammatical aspects of cohesion that is as much as 18 reference, the substitution can not be found, 7 elipsis, and 11 conjunction. While the aspect of lexical cohesion found 21 repetition, synonym 2, hypernim 1, collocation 1. The reseacrh result indicates that on grammatical cohesion is found most frequently used reference that sereves to anchance the reader’s understanding of the word referred. On the lexical cohesion the repetition is often used to emphasize information to readers of magazine. Keywords: Discourse analysis, grammatical cohesion, lexical cohesion